Impact of an intervention program to improve well-being of residents in Abu Dhabi, United Arab Emirates - Al Ghailani, Bushra; Al Nuaimi, Mouza; Al Mazrouei, Asma; Al Shehhi, Eiman; Beshyah, Salem; Al Fahim, Maha; Darwish, Ebtihal (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Background: Residency is a stressful period in physicians' life. During this period, residents are subjected to fatigue, depression, anxiety, and burnout. In 2016, we did our first study in Abu Dhabi hospitals to investigate residents' well-being; we found that 86.4% of residents were stressed, 50.8% of them were depressed, and 65.7% of the residents felt emotionally exhausted. Following this study, we introduced interventions to improve residents' well-being in Sheikh Khalifa Medical City (SKMC) residency programs. Objectives: To assess the difference between the well-being of residents in the year 2018 compared to 2016 after the implementation of interventions to SKMC residents. Methods: Following the initial cross-sectional surveys, interventions were made to improve residents' well-being. Repeated cross-sectional surveys were done to compare between the two periods and quantify the change. Results: The percentage of nonsmokers increased in phase 2 from 90% to 94%. The percentage of residents who exercise 1–2 times a week increased from 37.6% to 40.7%. The prevalence of perceived depression was 80% in phase 1 and become 82.4% in phase 2. In phase 1, 89% felt emotionally exhausted compared to 85.5% in phase 2. 28.3% and 22.4% of the residents felt always stressed in phase 1 and 2, respectively. The percentage of residents who are satisfied with their job was 31.7% in phase 1 but improved to 55.3% in phase 2. Conclusions: Residents' well-being and satisfaction of their work improved in our research after interventions. The percentage of those who were feeling emotionally exhausted and stressed also improved in phase 2.
Keywords: Abu Dhabi; educational intervention; postgraduate training; residents; residents' well-being; United Arab Emirates